Authority in contention - Myers, Daniel J.; Cress, Daniel M. (Amsterdam ; Oxford : Elsevier, 2004)
In recent years, there has been a surge in social movement theorizing known as the contentious politics approach to studying political protest activity. In 2002, a conference sponsored by the Collective Behavior and Social Movements Section of the American Sociological Association was held at the University of Notre Dame to consider, in part, this development in field. But the conference organizers also wanted to consider more broadly what we collectively consider to be social movement research and theorizing. In part, this means moving beyond a state-centered view of contentious politics and toward a more open definition of what might be fruitfully examined by social movement theories - and in turn what might inform those theories even as we use then in more traditional social movement arenas. This volume represents some of the fruits of that conference and includes four sections that defines social movement authorities challenges beyond state targets, expands our notions of what constitutes repression of social movement activity, examines challenges to cultural authorities and processes, and illustrates the broader notions of authority challenge in three case studies of corporate systems. With this volume, "Research in Social Movements, Conflict and Change" celebrates its 25th anniversary and a history of publishing important, leading edge research and theorizing in the areas pf protest, social conflict, and political change.
Introduction : authority in contention / Daniel J. Myers and Daniel M. Cress -- Part I. Authority in contention: beyond challenges to the state -- Social movements as challenges to authority: resistance to an emerging conceptual hegemony / David A. Snow -- The targets of social movements: beyond a focus on the state / Nella Van Dyke, Sarah A. Soule and Verta A. Taylor -- Part II. Expanding notions of repression -- Controlling protest: new directions for research on the social control of protest / Jennifer Earl -- Soft repressions: ridicule, stigma, and silencing in gender based movements / Myra Marx Ferree -- Part III. Culture and movement challenges -- Performing protest: drag shows as tactical repertoire of the gay and lesbian movement / Verta Taylor, Leila J. Rupp and Joshua Gamson -- Disciples and dissenters: tactical choice and consequences in the Plowshares movement / Sharon Erickson Nepstad -- Culture in and outside institutions / Francesca Polletta -- Part IV. Challenges in corporate systems -- Working it out: the emergence and diffusion of the workplace movement for lesbians, gay, and bisexual rights / Nicole C. Raeburn -- The American labor movement's (surprising) economic impact: how unions challenge consumerism and corporate governance / Teresa Ghilarducci -- Embodied health movements and challenges to the dominant epidemiological paradigm / Stephan Zavestoski ... [et al.] -- Authorities in contention / Daniel M. Cress and Daniel J. Meyers.
Title from e-book title screen (viewed Oct. 6, 2007).
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social movements -- Political aspects -- Congresses; Authority -- Congresses; Political persecution -- Congresses; Political control & freedoms; Political Science -- Political Freedom & Security -- General